Influencing Factors of Delayed Alcohol Consumption Among Adolescent in Secondary School - Valgerður Steingrímsdóttir 1987- (2014)
Much progress has been made in the delaying of alcohol consumption among adolescent in the United States and Iceland. The progress in Iceland can be traced to use of the Icelandic model that focuses on the social environment of the adolescent. It has received attention especially for how rapidly alcohol consumption among adolescents has changed following use of the model. However despite this change the increase in consumption from the last grade in compulsory schools up to secondary school is strong. The goal of the present study was to examine factors that might delay onset of alcohol consumption among adolescent in secondary schools. Data from ISCRA was used from a sample of 2000 students’ age 15-20 years old. The hypothesis was that certain factors lead to the adolescent not starting to drink alcohol; high monitoring, low alcohol consumption of friends, low alcohol consumption of parents and participation in sports. The results showed that all of the factors were a predictor for delayed onset of drinking except for the drinking habits of the father. Also there was a difference between predictability of the factors for the younger students compared to the older ones. Töluverður árangur hefur náðst bæði á Íslandi og í Bandaríkjunum í því að seinka neyslu áfengis á meðal unglinga. Hugarfarsbreyting hefur átt sér stað á Íslandi sem má rekja til notkunar á Íslenska módelinu sem leggur áherslu á félagslegt umhverfi unglingsins. Það hefur vakið athygli hversu hratt áfengisneysla meðal ungs fólks hefur minnkað í kjölfar notkunar á módelinu. Þrátt fyrir þessar framfarir sést ennþá mikil aukning í drykkju þegar unglingar færast frá efsta bekk grunnskóla upp í menntaskóla. Markmið þessarar rannsóknar var að rannsaka hvaða þættir það eru sem að hafa áhrif á að unglingar byrja ekki að neyta áfengis í framhaldsskóla. Í rannsókninni voru fyrirliggjandi gögn fengin frá Rannsóknum og greiningu. Úrtakið voru 2000 nemendur frá 15-20 ára. Tilgátur rannsóknarinnar voru að eftirfarandi þættir hefðu áhrif á að ungt fólk byrjaði ...